PERANAN KINERJA PEGAWAI DALAM MENINGKATKAN EFEKTIVITAS ORGANISASI DI DINAS KESEHATAN KABUPATEN KAUR - Hartati, Ruli (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Employees are actors who play an active role in carrying out tasks in the organization, according to their field of work. Therefore, employees as members of the organization are required to have good and optimal performance, so that the organization can run effectively. The important role of employee performance in improving organizational effectiveness encouraged the author to conduct research on the role of performance in improving the organization at the Kaur District Health Service. The Kaur District Health Service was chosen for research because the Health Service is closely related to public health. Research on employee performance focuses on the quality of work results, timeliness, initiative and communication. Meanwhile, organizational effectiveness is focused on achieving goals, integration and adaptation. The aim of this research is to analyze the role of employee performance in increasing organizational effectiveness. The main data source is a primary source from Health Service employees as informants. The technique used in data collection is interviews. Meanwhile, data analysis was carried out descriptively qualitatively. The results of the research conducted show that employee performance from the 4 aspects studied is not all good, as a result employee performance has not been able to increase organizational effectiveness optimally, because organizational effectiveness is not yet optimal.